Faktor yang Mempengaruhi Rendahnya Kualitas Pekerjaan Konstruksi Jalan di Pasaman Regency - Zulhanif, Zulhanif; Hasan, Alizar; Mulyani, Rini (Jurnal Talenta Sipil, 2024)
In an effort to meet the needs for optimum road facilities and infrastructure, through the Public Works and Spatial Planning Department, every year there are road construction and improvement activities in Pasaman Regency. The quality of road construction and improvement projects in Pasaman Regency is relatively low, so researchers conducted an analysis of the things that influence this low quality. The aim of this research is to identify factors that influence the low quality of road improvement and construction projects in Pasaman Regency and analyze the dominant factors. The data collection technique was carried out using a quantitative method, namely distributing questionnaires to respondents. Next, data processing was carried out by testing validity, reliability and factor analysis using SPSS. The results of the research conducted showed that there were 6 factors that influenced the low quality of road improvement and construction projects in Pasaman Regency, namely environmental and technical factors 16.686%, work method factors 12.047%, equipment factors 10.971%, labor factors 10.039%, managerial factors 8.648%, and external factors 7.999%. The dominant factors influencing the low quality of construction work in road improvement and construction in Pasaman district are environmental and technical factors, which consist of the response of the surrounding environment regarding project safety; existing and physical characteristics of buildings around the location; natural disasters; material prices; and funding at the contractor.